2019
DOI: 10.1108/et-04-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial competences in a higher education business plan course

Abstract: Purpose The purpose of this paper is twofold: first, to study which perceived and attained entrepreneurial competences acquired by students while developing a business plan are rated most highly; and second, to analyse the differences observed in entrepreneurial competences, depending on whether the business plan developed is real or fictitious. Design/methodology/approach To analyse the role played by business plans in perceptions and attainment of competence, data were collected from students enrolled on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 34 publications
3
51
0
7
Order By: Relevance
“…Zhang et al (2018) found that students will high possibility want to become an entrepreneur if they expose with entrepreneurial learning activities. Hence, Ferreras-Garcia et al ( 2019 ) indicated that individuals’ entrepreneurial mentality could be formed through the entrepreneurial education learning process. Moreover, Furthermore, Kabir et al ( 2017 ) proved that there is a relationship between entrepreneurial education and entrepreneurial intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al (2018) found that students will high possibility want to become an entrepreneur if they expose with entrepreneurial learning activities. Hence, Ferreras-Garcia et al ( 2019 ) indicated that individuals’ entrepreneurial mentality could be formed through the entrepreneurial education learning process. Moreover, Furthermore, Kabir et al ( 2017 ) proved that there is a relationship between entrepreneurial education and entrepreneurial intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In more sophisticated cases, the young generation demands in-depth development of entrepreneurial marketing skills for students who work and study within the entrepreneurial teams, e.g., in 2018, Petrylaite [31] explored a case of an SME marketing model application within higher education entrepreneurial teams. The creation of the business plan was a highly-rated activity that empowered the students' entrepreneurial competence [32].…”
Section: Introductionmentioning
confidence: 99%
“…The competence-based approach to education is one of the most significant changes implemented by the European Higher Education Area, with a shift from a content-centred model to a competence-based one, in which competences become the core element of the learning proces. [22] The competences included in graduate training will enable the generation will be ready to do business. Primary research can provide the necessary information to determine the current set of business competencies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%